Impact of viral eradication by direct-acting antivirals on clinical outcomes after curative treatment for hepatitis C virus-associated hepatocellular carcinoma - Yuko Nagaoki; Kenji Yamaoka; Yasutoshi Fujii; Shinsuke Uchikawa; Hatsue Fujino; Atsushi Ono; Eisuke Murakami; Tomokazu Kawaoka; Daiki Miki; Hiroshi Aikata; Clair Nelson Hayes; Masataka Tsuge; et al. (Therapeutic Advances in Gastroenterology)
Background: It is not clear that antiviral therapy for hepatitis C virus (HCV) after recovery from curative treatment for hepatocellular carcinoma (HCC) has an effect on suppressing recurrence or improving survival rates. Objectives: We analyzed the impact of eradication by interferon (IFN)-free direct-acting antiviral (DAA) therapy on clinical outcomes of patients with HCV-associated HCC who underwent curative treatment. Design: This was a retrospective study. Methods: We retrospectively reviewed 109 consecutive patients with sustained virologic response with DAA therapy after HCC treatment and analyzed HCC recurrence and overall survival (OS). Among these patients are those with a history of HCC recurrence and curative HCC treatments administered as definitive HCC treatments prior to initiation of DAA therapy. Results: Among 109 patients, 64 received DAA therapy after curative treatment for HCC; the remaining 45 received ⩾2 subsequent treatments for HCC. Cumulative HCC recurrence rates at 1, 3, and 5 years were 23%, 47%, and 56%, respectively. Multivariate analysis identified predictive factors for suppression of HCC recurrence as tumor number (hazard ratio (HR) 2.293 for multiple; p  = 0.006) and number of HCC treatments before DAA therapy (HR 2.928 for ⩾2; p  = 0.001). Among 64 patients who received curative treatment for HCC, cumulative first HCC recurrence rates at 1, 3, and 5 years were 12%, 34%, and 44%, respectively, second recurrence rates were 11%, 28%, and 39%, and third recurrence rates were 0%, 22%, and 53%, respectively; recurrence tended to be suppressed until 3 years. Cumulative OS rates at 3 and 5 years were 87% and 75%, respectively. On multivariate analysis, tumor number (HR 2.452 for single; p  = 0.026) was the only independent predictor of OS. Conclusion: DAA therapy after curative treatment for HCC suppresses HCC recurrence in the long term, but recurrence was higher in patients with a history of many HCC treatments.